2023
DOI: 10.1021/acs.orglett.3c00357
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed, Enantioselective Hydrofluoromethylation of Olefins: Access to Chiral α-Fluoromethylated Amides and Esters

Abstract: We herein report the nickel-catalyzed enantioselective hydrofluoromethylation of enamides and enol esters with CH 2 FI as the fluoromethyl source to enable the diversity-oriented synthesis (DOS) of chiral α-fluoromethylated amides as well as esters with features of wide functional group compatibility as well as excellent enantioselectivity. The synthetic value of this protocol was demonstrated by transformations of the resulted α-fluoromethylated amides to different scaffolds including amine, oxazoline, thiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In 2023, Li, Huang and co-workers reported that a BOX ligand ( L28 ) tuned NiH-catalyzed enantioselective hydrofluoromethylation of alkenes, which afforded α-fluoromethylated amides or esters in good yields with excellent enantioselectivities (Scheme 52). 86…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, Li, Huang and co-workers reported that a BOX ligand ( L28 ) tuned NiH-catalyzed enantioselective hydrofluoromethylation of alkenes, which afforded α-fluoromethylated amides or esters in good yields with excellent enantioselectivities (Scheme 52). 86…”
Section: Introductionmentioning
confidence: 99%
“…Notable successes have been obtained with CuH complexes as reported in the pioneering works of the Miura and Buchwald groups. , Furthermore, CoH ,− and FeH , complexes have also shown potential in such reactions. Due to the unique reactivity and a variety of oxidation states of nickel ranging from Ni(0) to Ni­(IV), research concerning NiH-catalyzed reactions has attracted more attention. , One research interest in this area has focused on the NiH complex-catalyzed hydroamination of alkenes with different nitrogen sources (Scheme a). For example, the groups of Hu and Wang reported the nickel-catalyzed hydroamination of alkenes with electrophilic anthranils .…”
mentioning
confidence: 99%